Video performance over ad hoc wireless local area network - Tan, Chong Eng (Universiti Malaysia Sarawak (UNIMAS), 1999)
This thesis project first introduces the wireless LANs technology and its standards, lEEE 802.1 1. Standards covered here mainly concentrate on the ad hoc wireless LAN operating at 915MHz using direct sequence spread spectrum radio frequency. The MAC sublayer, frame format, medium access methods, and physical layer are discussed. Simulation model, throughput analysis, and simulation parameters are introduced as well. The main objective of the project is to determine a set of system parameters which allow successful implementation of MPEG-1 video transmissions over-ad hoc wireless LAN. Video performance evaluations are used to determine the parameters and its efficiency. The experiment first stressed on the PC system parameters determination for delivering MPEG-1 video over a single peer-to-peer wireless channel. The parameters involved are processor clock speed and architectures, video bus and accelerations, software decoder technology, operating systems, and the signal-to-noise ratio (SNR). The second part of the experiment is focus on the video performance evaluation for simultaneous multi-peer transmissions. The objective of this experiment is to evaluate the efficiency of the wireless LAN Medium Access Control (MAC) in handling multiple simultaneous MPEG-1 video transmissions over a single wireless channel. The method for overcome the constraint of delivering multiple MPEG- 1 videos over the limited 2 Mbps wireless channel also discussed here. The last part of the experiment concentrate on the video performance over integrated network. Video performance evaluation is conducted across an integrated wired-wireless network via a PC-based IP router. Through the experiment, the video performance over a routed network environment using TCPIIP protocol could be determined. In the conclusions and discussions section, a set of guideline for the implementation of video transmission over wireless LAN is presented. Some experiment limitations and future works are proposed.